Activity Based Costing-Sebuah Kajian - Putuhena, Hempry; Kamarudin, Sitti Fatimah (Politeknik Ganesha Medan, 2024)
The unit cost calculation method with Activity Based Costing (ABC) is an efficient system. This system is certainly a system that is far more accurate than the traditional system. It is important for a company to know the units of the product or service it produces. Unit cost information becomes important for managerial decision making. The importance of the right decision certainly requires the company to use the right calculation method. Thus this study conducts a study of the ABC method that can be utilized properly by companies. This research method is a literature study conducted to gain more understanding of Activity based costing (ABC) research. This study carried out the stages starting from selecting topics, collecting literature, to reviewing the literature. The results of this study indicate that the application of this method requires a large commitment and resources from the organization and if this is fully implemented then the quality of the use of this method is very beneficial for companies in decision making